COMMUNICATION SKILLS AND TEACHING-LEARNING STRATEGIES: PERCEPTION OF NURSING STUDENTS - Camila Dalcól; Mara Lúcia Garanhani; Lígia Fahl Fonseca; Brígida Gimenez Carvalho (Universidade Federal do Paraná, 2018)
Objective: To understand the perceptions of nursing students about the teaching-learning strategies for the development of communication skills in an integrated curriculum. Method: qualitative-comprehensive, of case-study type, with 55 undergraduate nursing students from a public university in southern Brazil, in October 2014 and August 2015, through 6 focus groups, recorded, transcribed in full and submitted to Bardin content analysis. Results: The strategies used to develop the communication were theoretical classes, tutorial, seminar, written evaluation, portfolio, training, the Interdisciplinary and Multiprofessional Practices, nursing internship and feedback. Conclusion: The curriculum examined favored the development of communication skills through the use of active methodologies and modular structuring.